Exploring The Dynamics Of Tax Avoidance On Firm Value: Insights From Recent Research Trends And Cluster Analysis - Oktavia, Windy Dwi; Indarwati , Tias Andarini; Kautsar , Achmad (CV ODIS, 2024)
This study examines the relationship between tax avoidance and firm value, a topic that has gained importance in recent years. The study highlights tax avoidance strategies that involve various methods such as tax deferral, tax arbitrage, and income manipulation to reduce tax liabilities. The findings indicate that effective tax avoidance practices can enhance corporate value; however, this relationship is influenced by factors such as corporate governance structure, ethical considerations, and the regulatory environment. The study employs VOS Viewer to analyze data from 71 relevant articles identified from the Scopus-ScienceDirect database across six major fields, including Business, Management, and Accounting, as well as Social Sciences. Cluster analysis reveals three primary focuses: tax avoidance, firm value, and tax planning. The first cluster indicates that tax avoidance can influence investor perception and valuation, while the second cluster examines how effective tax planning can improve a company's financial performance. The third cluster explores the relationship between tax avoidance and firm value, emphasizing the importance of in-depth analysis to understand the interaction between tax strategies, governance mechanisms, and investor perceptions. The research findings show that the topics of tax avoidance and firm value evolved from 2019 to 2021, with the main concentration on the topics of firm, firm value, and tax avoidance, as well as several smaller but significant topics.